EFFECT OF PANCHKARMA ON PREMATURE - Chopra, Geeta; Kapil, Soni; Bhardwaj, Anil; Shukla, Seema (International Research Journal of Ayurveda & Yoga, 2020)
Premature ovarian failure is defined as ovarian failure before the age of forty. In modern medicine only hormonal replacement therapy is available as treatment. HRT itself has its own side- effects. So, we have selected patient who was on hormonal pills since last 5-6 years on and off but didn’t get relief despite of hormonal pills. A study was done in RGGPG Hospital, Paprola. A Patient of 35 years, Primipara , who was having complaint of irregular menses with scanty menses since 7-8years. Hot flushes, Insomnia since 5-6 years. Absence of menses since 3 months. Associated complaints: Vaginal dryness, Dryness of skin, Stress incontinence, Hair fall and brittleness of nails. As the disease is vatapitta predominant where symptoms like hot flushes, sweating showing pittaj characteristic whereas Insomnia, depression, vaginal dryness, brittleness of nail showing vataj characteristic. So, we planned a treatment protocol after stopping hormonal pills –virechana, basti, nasya, takradhara along with some oral medications. Where virechan karma with haritaki churna and erand tail to alleviate pittaj symptoms. Basti (Niruha with dashmoola kwath) and uttarbasti with phalaghrita to alleviate vataj symptoms. Nasya (Shodhan nasya with trikatu churana,Shaman nasya with sadbindu tail).Takradhara with amalaki, musta, takra . After shodhan chikitsa shaman chikitsa was continued .On evaluation of effect of treatment –overall result was marked improvement in all the symptoms .Symptomatic relief persisted even after 1 month of completion of panchkarma therapy.